Study of DKI Jakarta Public Perceptions on the Revitalization of the Transjakarta BRT (Bus Rapid Transit) Bus Stop at Bundaran Hotel Indonesia - Razak, Nuvika; Susilo, Budi Hartanto (Jurnal Teknik Sipil, 2025)
Bundaran HI bus stop is one of the public transportation system infrastructures where this bus stop is one of the busiest due to the change in transportation modes. Currently, the bus stop looks more modern, narrow, crowded, and uncomfortable for service users. This is used for commercial purposes as a place for taking pictures and tourism. The research objective is to analyze the influence of facilities and service quality on BRT passenger loyalty, to determine the level of customer satisfaction that influences BRT services and to determine the perception of BRT users towards the revitalization of the bus stop. The method chosen is quantitative with data collected through a questionnaire survey of 442 respondents. The analysis method uses descriptive statistics and inferential statistics. Non-parametric statistical tests with Mann Whitney. While the customer satisfaction test uses a Likert scale. The results of the Mann Whitney test study where the Asymp.Sig. (2 tailed) value of 0.032 is smaller than the probability of 0.05, meaning that there is an influence of facilities and service quality on service user loyalty. A satisfaction level of 25% means dissatisfied/less good. Public perception of the revitalization of the Bundaran HI bus stop is negative. The recommendations for the government do not need to be built excessively and luxuriously, so that it does not become an example for other big cities. There is need to be a typical bus stop whose functions and benefits can be imitated, such as getting used to reading literature while waiting for the bus to arrive.